Delegation of competences and criminal compliance: A study on the transfer and transformation of duties (of supervision) in economic criminal law - Gómez Martín, Víctor (2020)
Delegation is usually defined as that technique through which the delegate is discharged of initial functions and competences, transferring them to the delegate and thereby producing a transformation of the individual responsibility spheres of both the first and second. In the delegation, the position of guarantor of the delegate would correspond to the responsibility for authorship regarding the unavoidable result, while the responsibility of thedelegate would be that of criminal participation. The businessman, therefore, would not extinguish his position as guarantor, but would modify it, so that the duties of control and avoidance of harmful events would become duties of supervision and monitoring of the delegate’s work.